Peran Strategis Guru Dalam Meningkatkan Motivasi Belajar Siswa di Sekolah Dasar - Rahmat Ramadan; Sarintan N. Kaharu; Nuraini Nuraini; Zulnuraini Zulnuraini; Nurgan Tadeko (Institut Agama Islam Daruttaqwa Gresik, 2025)
Learning motivation is a crucial factor that determines the success of education at the elementary school level. However, some students still exhibit low motivation despite the teacher's efforts to create engaging learning experiences. This study aims to explore the teacher's role as a motivator in enhancing the learning motivation of fifth-grade students at SDN 1 Sindue. A descriptive qualitative approach was used, with data collection through observation, interviews, and documentation involving one teacher and six students categorized as having high and low motivation. The results show that the teacher implemented various strategies such as stimulating learning interest, creating a pleasant atmosphere, giving praise, assessments, rewards, and competitions. These strategies were found effective in increasing motivation for most students, although some students faced internal obstacles such as laziness and lack of self-confidence, as well as external obstacles like difficulty with the material and an unfavorable learning environment. The study highlights the importance of individualized and adaptive approaches by teachers to sustain student learning motivation. The implications of this research emphasize the need for teacher training in implementing more personal and context-specific motivational strategies. This study also contributes to the literature on learning motivation at the elementary level through an empirically grounded, context-specific approach.